Cultural rule orientation, legal institutions, and the credibility of corporate social responsibility reports - Tobias Steindl (Corporate Social Responsibility and Environmental Management, 2020)
Culture matters for credible corporate social responsibility (CSR) reporting. I show that firms located in countries with stronger cultural rule orientation are more likely to (a) receive assurance on their CSR report, (b) receive assurance from an accounting firm, (c) receive assurance in accordance with an assurance standard, and (d) receive assurance on their entire CSR report. Path analysis reveals that the direct effect of cultural rule orientation is much stronger than its indirect effect via legal institutions. I confirm the dominance of the direct effect in a qualitative comparative analysis. The economic significance of the direct effect is identified using probit regression analysis. Endogeneity concerns are addressed in a battery of robustness checks. Overall, the findings of this study provide a nuanced understanding of how culture affects credible CSR reporting, which, in turn, has important implications for managers, stakeholders, and policy makers.
Keywords: 650; assurance; corporate social responsibility; culture; legal institutions; rule orientation; sustainable development; uncertainty avoidance